2018
DOI: 10.1121/1.5041261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequency mismatch and band partitioning on vocal tract length perception in vocoder simulations of cochlear implant processing

Abstract: The vocal tract length (VTL) of a speaker is an important voice cue that aids speech intelligibility in multi-talker situations. However, cochlear implant (CI) users demonstrate poor VTL sensitivity. This may be partially caused by the mismatch between frequencies received by the implant and those corresponding to places of stimulation along the cochlea. This mismatch can distort formant spacing, where VTL cues are encoded. In this study, the effects of frequency mismatch and band partitioning on VTL sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…Since sensitivity to both F0 and VTL cues was found to be related to overall SoS performance, the question then arises of whether improving one measure would necessarily lead to an improvement in the other. In a previous study, VTL JNDs were found to depend on the frequency-to-electrode allocation mapping in vocoder simulations of CI processing (El Boghdady et al, 2018). It remains to be seen whether implant parameters, such as the frequency-to-electrode allocation mapping or the coding strategy, could help improve SoS performance in addition to JNDs.…”
Section: Discussionmentioning
confidence: 92%
“…Since sensitivity to both F0 and VTL cues was found to be related to overall SoS performance, the question then arises of whether improving one measure would necessarily lead to an improvement in the other. In a previous study, VTL JNDs were found to depend on the frequency-to-electrode allocation mapping in vocoder simulations of CI processing (El Boghdady et al, 2018). It remains to be seen whether implant parameters, such as the frequency-to-electrode allocation mapping or the coding strategy, could help improve SoS performance in addition to JNDs.…”
Section: Discussionmentioning
confidence: 92%
“…This raises the question of whether CIs could be fitted with the goal of mitigating the effect of decreased spectrotemporal resolution that may arise from channel interaction. Several studies (e.g., Di Nardo et al., 2011 ; El Boghdady et al., 2018 ; Fitzgerald et al., 2013 ; Fu & Shannon, 1999 ; Grasmeder et al., 2014 ; Leigh et al., 2004 ; McKay & Henshall, 2002 ; Omran et al., 2011 ) have proposed that optimizing the frequency-to-electrode allocation map could have the potential to address the limited spectral resolution in the implant. More specifically, using vocoder simulations, El Boghdady et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (e.g., Di Nardo et al, 2011;El Boghdady et al, 2018;Fitzgerald et al, 2013;Fu & Shannon, 1999;Grasmeder et al, 2014;Leigh et al, 2004;McKay & Henshall, 2002;Omran et al, 2011) have proposed that optimizing the frequency-to-electrode allocation map could have the potential to address the limited spectral resolution in the implant. More specifically, using vocoder simulations, El Boghdady et al (2018) have shown that the frequency-to-electrode allocation map could have a direct influence on VTL JNDs and that the frequency mapping, if optimally fitted, could help reduce the detrimental effects of channel interaction and frequency mismatch in the cochlea on VTL JNDs. These studies help to pave the way for investigating whether the CI parameters (such as the frequency allocation map) or signal processing could be optimized in a way to improve both SoS perception and the sensitivity to voice cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question of whether CIs could be fitted with the goal of mitigating the effect of decreased spectrotemporal resolution that may arise from channel interaction. Several studies (e.g., Di Nardo, Scorpecci, Giannantonio, Cianfrone, & Paludetti, 2011;El Boghdady et al, 2018;Fitzgerald, Sagi, Morbiwala, Tan, & Svirsky, 2013;Fu & Shannon, 1999;Grasmeder, Verschuur, & Batty, 2014;Leigh, Henshall, & McKay, 2004;McKay & Henshall, 2002Omran, Lai, & Dillier, 2011) have proposed that optimizing the frequency-to-electrode allocation map could have the potential to address the limited spectral resolution in the implant. More specifically, using vocoder simulations, El Boghdady et al (2018) have shown that the frequency-to-electrode allocation map could have a direct influence on VTL JNDs, and that the frequency mapping, if optimally fitted, could help reduce the detrimental effects of channel interaction and frequency mismatch in the cochlea on VTL JNDs.…”
Section: Discussionmentioning
confidence: 99%